Relatively spared central multifocal electroretinogram responses in acute quinine toxicity. (8th July 2011) - Saeed, Muhammad Usman; Noonan, Carmel; Hagan, Richard; Brown, Malcolm
Abstract : A 71-year-old man was investigated with electrodiagnostic testing 4 months after a deliberate quinine overdose. Initially he was admitted to intensive care unit with visual acuity (VA) of perception of light in both eyes. VA recovered to 6/6 right eye and 6/12 left eye, though severely constricted fields were noted. Slow stimulus (base period of 83 ms) multifocal electroretinogram (ERG) showed electronegative responses outside the inner 5 degrees, with a reduced but electropositive response seen in this central area. It appears that in this case of bilaterally negative ERGs that the macula/fovea (which has a vascular supply through the choroid) is relatively spared as is seen in bilateral vascular electronegative ERGs. This may indicate that quinine toxicity to the retina may be secondary to effects similar to vascular occlusion or severe ischemia during the acute phase of quinine poisoning.